2016
DOI: 10.18632/oncotarget.12907
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical margin status on the outcome of bladder cancer treated by radical cystectomy: a meta-analysis

Abstract: Data regarding the association between surgical margin status and the outcome of bladder cancer treated by radical cystectomy (RC) are conflicting. Therefore, the present meta-analysis was performed to assess the associations between the outcomes of bladder cancer, in terms of recurrence-free survival (RFS), cancer-specific survival (CSS) and overall survival (OS), and the presence of positive surgical margins versus negative surgical margins following treatment with RC. Research articles published prior to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…Table 3 summarizes the oncological end-points from traditional ORC series from high-volume centers, as well as RARC versus ORC series, including the 4 RCTs and meta-analyses. [ 41 44 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 ] An overall conclusion that can be drawn from the above studies, further supported by the fact that long-term data are now available, is that RARC is equivalent to ORC in terms of oncological efficacy.…”
Section: Survival Outcome Measuresmentioning
confidence: 89%
“…Table 3 summarizes the oncological end-points from traditional ORC series from high-volume centers, as well as RARC versus ORC series, including the 4 RCTs and meta-analyses. [ 41 44 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 ] An overall conclusion that can be drawn from the above studies, further supported by the fact that long-term data are now available, is that RARC is equivalent to ORC in terms of oncological efficacy.…”
Section: Survival Outcome Measuresmentioning
confidence: 89%
“…PSMs have been recognized as an adverse prognostic sign for disease prognosis or local recurrence, and thus, NSS may theoretically decrease the probability of complete tumor resection (33). In previous research, the unfavorable effect of PSMs has been described for different types of cancers including: prostate (34), rectal (35), and bladder cancer (36). More recently, the clinical importance of PSMs in RCC patients after NSS was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The first meta-analysis showed that positive surgical margins have a negative and statistically significant impact in the survival outcome measures. 64 Most of the studies show a trend for better outcomes of RARC, but these are not statistically significant. Furthermore, all systematic reviews and the meta-analysis of RCTs concur that RARC and ORC have equal margin rates.…”
Section: Oncological Outcomesmentioning
confidence: 92%
“…Apart from lymph node dissection, it is also critical to extirpate the disease fully, as reflected by the margin status. The first meta‐analysis showed that positive surgical margins have a negative and statistically significant impact in the survival outcome measures …”
Section: Oncological Outcomesmentioning
confidence: 99%